EXPERIMENTAL STUDIES OF THE ADAPTIVE HUDRAULIC SYSTEM ON THE BASE OF THE DISTRIBUTION VALVE WITH PROPORTIONAL ELECTROHYDRAULIC CONTROL - Pylavets, Volodymyr; Tovkach, Artem; Kozlov, Leonid; Burenikov, Yurii; Kravchuk, Olexandre (Scientific Works of Vinnytsia National Technical University, 2020)
Stable trend of the development of the hydraulic systems of mobile operation machines is the transition to the application of the regulated pumps and hydraulic devices with the proportional electric hydraulic control. In such hydraulic systems the correspondence of pumps capacity to the flow volume, consumed by the hydraulic motors as well as proportionality of the pressure value in the hydraulic system to the loading on the hydraulic motor or the most loaded of the several hydraulic motors is provided. Mobile machines equipped with such hydraulic systems can efficiently operate with wide range of the changeable working tools, providing high quality of the work and loading of the machines during a year. Besides, the proportional control in the hydraulic systems of this type provides high accuracy of the operation execution and greatly improves the working conditions of the operators. The paper considers the adaptive hydraulic system on the base of the distribution valve with proportional electrohydraulic control. Experimental stand for testing the adaptive hydraulic system was constructed. The hydraulic diagram of the distribution valve and the construction of the operation unit is presented. The distribution valve provides the possibility of the remote proportional electromagnetic control of the flow from the controller with the possibility of the stabilization of the hydraulic motors motion speed. Adaptive hydraulic system provides the possibility of the coordination of the hydraulic motors motion speed. The metrologic characteristic of the stand is given , which enables to control the value of the pressure in the hydraulic system, current and voltage values in the control lines, number of rotations of the hydraulic motor and registrate the dependences of the pressure values in the hydraulic system on the time if load changes. It was determined that the error of the flow value stabilization across the distribution valve does not exceed 6.8 %, in the studied range of the load change and the value of the flow changes proportionally according to the signal, sent from the controller. Regulation time in the hydraulic system on the base of the developed distribution valve did not exceed sec in the range of the pressure change МPа and the output of the pump m3/sec.